Identification of Chemical Composition and Metal Determination of Retama raetam (Forssk) Stem Constituents Using ICP-MS, GC-MS-MS, and DART-MS - Al-Onazi, Wedad (J Anal Methods Chem, 2021)
This study aims to investigate the chemical constituents of the stem of Retama raetam growing in Saudi Arabia. The organic and inorganic composition of ethanol extract of R. raetam stem has been explored using direct analysis in real time-mass spectrometry (DART-MS), gas chromatography-mass spectrometry (GC-MS), and inductively coupled plasma-mass spectrometry (ICP-MS). Analysis conducted by DART-MS and GC-MS reveals the presence of several interesting organic constituents identified as 2,4-di-tert-butylphenol, sparteine, benzenepropanoic acid, 3,5-bis(1,1-dimethylethyl)-4-hydroxy-, methyl ester, phthalic acid, 1-octadecanol, squalene, argentamin, 2,4-di-tert-butylphenol, sparteine, benzene propanoic acid, 3,5-bis(1,1-dimethylethyl)-4-hydroxy-, methyl ester, phthalic acid, 1-octadecanol, squalene, argentamin, and hentriacontane in the ethanol extract of the R. raetam stem. The ICP-MS analysis of stem extract showed the presence of a significant amount of important inorganic elements including aluminum, chlorine, calcium, bromine magnesium, phosphorus, scandium, and chromium. The current study complements other R. raetam extract investigations carried out in the past and provides the additional data for the future research studies.